Dynamics of the Carbonate System Across the Peruvian Oxygen Minimum Zone - Hernandez-Ayon, Jose M.; Paulmier, Aurélien; Garcon, Veronique; Sudre, Joel; Montes, Ivonne; Chapa-Balcorta, Cecilia; Durante, Giovanni; Dewitte, Boris; Maes, Cristophe; Bretagnon, Marine (Frontiers in Marine Science, 2019)
The oxygen minimum zone (OMZ) of Peru is recognized as a source of CO2 to the atmosphere due to upwelling that brings water with high concentrations of dissolved inorganic carbon (DIC) to the surface. However, the influence of OMZ dynamics on the carbonate system remains poorly understood given a lack of direct observations. This study examines the influence of a coastal Eastern South Pacific OMZ on carbonate system dynamics based on a multidisciplinary cruise that took place in 2014. During the cruise, onboard DIC and pH measurements were used to estimate pCO2 and to calculate the calcium carbonate saturation state (Ω aragonite and calcite). South of Chimbote (9oS), water stratification decreased and both the oxycline and carbocline moved from 150 m depth to 20-50 m below the surface. The aragonite saturation depth was observed to be close to 50 m. However, values less than 1.2 were detected close to 20 m along with low pH (minimum of 7.5), high pCO2 (maximum 1250 μatm), and high DIC concentrations (maximum 2300 μmol kg-1). These chemical characteristics are shown to be associated with Equatorial Subsurface Water (ESSW). Large spatial variability in surface values was also found. Part of this variability can be attributed to the influence of mesoscale eddies, which can modify the distribution of biogeochemical variables, such as the aragonite saturation horizon, in response to shallower (cyclonic eddies) or deeper (anticyclonic eddies) thermoclines. The analysis of a 21-year (1993-2014) data set of mean sea surface level anomalies (SSHa) derived from altimetry data indicated that a large variance associated with interannual timescales was present near the coast. However, 2014 was characterized by weak Kelvin activity, and physical forcing was more associated with eddy activity. Mesoscale activity modulates the position of the upper boundary of ESSW, which is associated with high DIC and influences the carbocline and aragonite saturation depths. Weighing the relative importance of each individual signal results in a better understanding of the biogeochemical processes present in the area.